General Considerations Regarding Management Accounting, Costs and their Classification: Array - Chira, Tatiana (The Journal of Accounting and Management, 2021)
Abstract. Modern trends in the integration of the Republic of Moldova into the European space show the need to harmonize internal accounting with the provisions of the European Union Directives and International Financial Reporting Standards. This also applies to cost accounting, which, being an integral part of the accounting system, must provide prompt and useful information in the decision-making process, starting with the composition of costs and ending with the preparation of management reports. The nominated information is used by a wide range of users to justify management decisions to determine the types of products (works, services) that will be produced (performed, provided) in the future or the production or delivery of which must be suspended, budgeting of production volumes and the results of the work of responsibility centers, as well as making decisions based on profit criteria. This indicates that the study of the methodology and practice of cost accounting, as well as the establishment of priority directions for their improvement are relevant and important both in theoretical and applied terms, which determined the purpose of the study in this article.